2014
DOI: 10.1097/bsd.0000000000000102
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes for Painless Drop Foot Due to Degenerative Lumbar Disorders

Abstract: Duration of palsy had the greatest effect on recovery. As the only goal of this surgery is improvement in the strength of the tibialis anterior, caution must be exercised when considering surgery for patients with longstanding palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 15 publications
0
24
1
Order By: Relevance
“…Prior work using traditional analytic approaches (such as multivariate analyses) have suggested that duration of drop foot before surgery and preoperative motor weakness [1,3,16,17] may be associated with recovery of active dorsiflexion after decompressive lumbar spine surgery; however, this is somewhat controversial, since other studies did not identify one or either of these factors as important in anticipating a patient's neurologic recovery [2,6,7,12,13,21]. We believe that those analytic approaches may not be ideal for this purpose because they are difficult to describe layered correlations among predictors, and we believe that Bayesian network analysis, which is graphic and intuitive to the clinician, may be better suited to the task because this approach readily describes the layered correlation among predictors.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Prior work using traditional analytic approaches (such as multivariate analyses) have suggested that duration of drop foot before surgery and preoperative motor weakness [1,3,16,17] may be associated with recovery of active dorsiflexion after decompressive lumbar spine surgery; however, this is somewhat controversial, since other studies did not identify one or either of these factors as important in anticipating a patient's neurologic recovery [2,6,7,12,13,21]. We believe that those analytic approaches may not be ideal for this purpose because they are difficult to describe layered correlations among predictors, and we believe that Bayesian network analysis, which is graphic and intuitive to the clinician, may be better suited to the task because this approach readily describes the layered correlation among predictors.…”
Section: Discussionmentioning
confidence: 83%
“…Predictors for residual drop foot in previous studies are varied, but the two main predictors have been preoperative motor weakness [1,3,6,12,16,17,21] and the duration of drop foot before surgery [2,3,7,16,17]. The former corresponds to pretibialis anterior muscle strength in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An arising problem in this pathway is being unable to move the extremities, which is called paresis. Isolated foot drop of a single leg is the weakness of the dorsiflexor muscles of the foot, and this usually arises painlessly due to peripheral neuropathy, such as peroneal nerve damage or radiculopathy 1 7) . Isolated painless foot drop is also caused by central origin, but this is rare, and there are only several reports of acute infarction mimicking peroneal neuropathy 4 5 9 10) .…”
Section: Discussionmentioning
confidence: 99%